Elucidating roles of lipid remodeling and ion homeostasis in sustaining oyster allometric growth - Guixiang He; Tuo Yao; Yang Xu; Yuewen Deng; Yong Liu; Liqiang Zhao (Aquaculture Reports)
Allometric growth provides a great opportunity for bivalve breeding programs. Despite its great success in accelerating shell growth and shortening breeding timelines, little effort has been devoted to improving other commercially important traits, particularly meat yield, through allometry. Here, we for the first time demonstrated the allometric growth of soft tissues in ecologically and economically important oysters (Crassostrea hongkongensis), and disentangled the underlying mechanisms. Compared to isometric individuals, oysters that exhibited striking allometric growth of tissues (i.e., extremely high meat yield) showed significantly increased activities of enzymes underpinning the energy metabolism, ion transport and antioxidant defence. A total of 61 significantly up-regulated lipid components (which were predominantly composed of glycerolipids and glycerophospholipids) were further observed in allometric oysters. In particular, lipids used for cell energy storage and membrane construction varied significantly, implying the occurrence of lipid remodeling which can likely play a central role in the regulation of cellular ion homeostasis. Transcriptome reshuffling following tissue allometry identified positive signaling pathways underpinning the transepithelial ion transport, energy metabolism and intercellular adhesion, especially with significant upregulation of genes related to the metabolism of epidermal growth factor. These findings demonstrate that allometric oysters can implement efficient mechanisms such as lipid remodeling and ion homeostasis to sustain rapid tissue growth, which in turn can be adopted for the selective breeding of marine bivalves to improve commercially important traits, especially meat yield, aside from shell growth.